Effect of Oxytocin Massage on Changes in Oxytocin Hormone Concentration in Pregnant Women - Samsir syam; St. Subriani (Viva Medika, 2024)
Background: Labour is a natural occurrence for every woman, but it may turn into a pathological condition if labour lasts too long. One non-pharmacological treatment method that is considered quite effective is oxytocin massage, which is known to stimulate labour contractions. Objective: This study aims to determine the effect of oxytocin massage on changes in oxytocin concentration of mothers in labour. Method: This study used quasi-experiment with purposive sampling technique. The number of samples was 32 people with massage actions performed on the spine using the thumb and knuckles. Data was tested using Chi Squre test, Mann Withney. Results: the study showed Oxytocin in Inpartu Kala I Latent Phase of the group that was massaged was higher than those who were not massaged although it was not significantly significant p=0.175. Significantly there is no effect of differences in Oxytocin Hormone Inpartu Kala I Active Phase (p=0.602). The concentration of oxytocin hormone in the group that was massaged in the first phase of latent labour was higher than that in the active phase, although it was not significant, p=0.076. Oxytocin concentration of the group that was not massaged inpartu Kala I Latent Phase was higher than the Active Phase although not significantly significant p=0.917. Conclusion: In the latent phase, the oxytocin concentration of the group that was massaged and not massaged had a significant difference and in the active phase there was no significant effect on the group